Health of long term benzodiazepine users. Issue 6622 (27th February 1988) - Rodrigo, E K; King, M B; Williams, P
Abstract : The physical and psychological health of long term (over one year) users of benzodiazepines in one general practice was assessed by patients' self reporting of illness and by general practitioners' records. Of 3741 patients registered with the practice, 82 had been prescribed a benzodiazepine, and 64 of these agreed to enter the study. All but five of these patients were over 40 years of age, nearly a third (19) were given a diagnosis related to depression by interviewers, and between a third and a half reported a current physical illness. Long term treatment with benzodiazepines is not necessarily optimum management but may reflect the realities of general practice.